Design and fabrication of easy assemble tricycle - Mohd Ali Amri, Muhammad Hassan (2008)
The study of manufacturing was very important in order to carried out this project to ensure that student understand on what are need to do. This project is about designing and fabrication the Easy Assemble Tricycle to give a recommendation for parents to bring out this tricycle wherever they want for their children to play. This project involves the process of designing the tricycle to simplify the children to using it. After the design has complete. It was transformed to its real product where the design is used for guideline. This project also require to ensure the safety for the indeed of publishing. Methods and process involve in this project for instance joining using welding, nut and bolt. This process is mainly about generating a new concept of Easy Assemble Tricycle that would make easier to assemble and easy to bring anywhere. This tricycle also cans reduce a space to store in. After all process had been done, this tricycle may help us to understand the fabrication and designing process that involved in this project.